MAKETING MIX FACTORS BRAND VALUE AND THE PURCHASING BEHAVIOR OF ADHESIVE TAPE AT CAPRIC COMPANY (THAILAND)., LTD., IN THE EASTERN REGION - Somhanwong , Nalatthaporn; Visitnitikija, Chinnaso (Journal of MCU Nakhondhat, 2024)
This research aims to study 1) the marketing mix factors of Capric company (Thailand) Ltd., 2) the brand value of the products, 3) the adhesive tape purchasing behavior of the buyers, 4) compare the adhesive tape purchasing behavior of the buyers classified by personal data, 5) marketing mix factors that are affect purchasing behavior of the buyers of Capric company, and 6) the product brand value affecting purchasing behavior of the buyers. The sampling groups of 120 buyers used a questionnaire to study, which was processed using percentages, mean, t - test, f - test (one - way ANOVA), and multiple regression analysis. The results of the study found that most respondents were female, aged 31 - 40 years, with a bachelor's degree, and business owners who had operated for more than 15 years. The buyers have been trading with the company for 1-5 years. The owners of the business are the ones who make the purchasing decisions and purchase adverse products. The overall picture of the marketing mix and brand value is high. The price and brand value factors in terms of brand loyalty significantly influence the company's adhesive tape purchasing behavior at the 0.05 level. Recommendations from the study are that products must be high quality and diverse. Products should be labeled clearly and show the product name, color, size, width, length, and standard packaging. The prices should be set appropriately to the quality and value of the products. Offer the choices and prices appropriate to the size and quality of the products. The distribution channels are diverse and on-time delivery. Offer the CRM program to the buyers for service satisfaction. There are routine checks monthly regarding all aspects of service satisfaction. There is continuous marketing promotion for buyers to meet the demands and requirements.